Networks of meaning : Communication trajectories in social sciences and humanities. (Sketch of a research problem) (2013)
ABSTRACT: The model of Networks of Meaning is useful for ordering and grouping different texts of science according to their contributions and shared trajectories. The tools used can be described metaphorically as a sieve used to filter texts according to their shared meaning. The model uses tools from scientometrics, network analysis and documentary analysis. Our purpose is presenting an alternative analytical model for observing the dynamics of scientific production for example: paths and trajectories in contributions to solve different problems; not only researchers but communities of researchers that built together different answers; and to know who knows what and where in a specific territory. This model is applied to social sciences and humanities. Here is problematized the situation of social sciences and humanities according to the model.